The promise of the city : space, identity, and politics in contemporary social thought - Tajbakhsh, Kian, 1962- (University of California Press, 2001)
This title proposes a theoretical grounding for the study of cities and the people who live and work in them, using a threefold, interdisciplinary approach to urban identities linking agency, space, and structure.